Early juvenile stages of three jewfishes from the southeast coast of India - Bensam, P (Indian Journal of Fisheries, 2011)
Three stages each of Johneiops vogleri, Johnius carouna and / . carulta, all collected form bottomtrawl catches off Tuticorin and Pono Novo have been described. An account of the changes undergonein the morphology and pigmentation is given. Certain notable differences between 2 younger stages ofJ. carulta described earlier are pointed out.